Folklore of Russian Resettlers in Context of Local Traditional Culture: Phenomenon of Wedding Ceremony in Arzamastsevo of Udmurt Republic - S. V. Tolkacheva (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The article is devoted to the specifics of the wedding ceremony in Arzamastsevo village of Karakulinskiy district of the Udmurt Republic (UR), where the Russian migrants from the Tambov province live since the first third of the XIX century. The history of the village is covered - documentary sources, stories, oral narratives. The local-group nicknames “yaguty,” “sleporody,” “slepushi,” the toponym “Arzamastsevo” are analysed. Elements of the wedding ceremony are characterized. Dialectal names to ritual actions are presented. Peculiar wedding customs are revealed - bride’s otbivaniye zori ; buddies’ riding of kurnik and the bride’s bed, stealing the bed; feast at the bride’s house after the wedding; stretching the filaments in the yard of the bride during the arrival of the bridegroom for the bride. The results are presented of a comparative analysis of wedding rituals of Arzamastsevo and other Russian dialect traditions of UR. It is established that the marriage rites of Arzamastsevo organically correlate with the Russian wedding folklore of Karakulinskiy district and other local traditions of UR. It is mentioned that the probable cause of this fact is that by the time Arzamastsevo arose on the territory of the Middle Kama region there had developed a strong local tradition, typologically close to the Russian traditional culture of the Central provinces of Russia. It is emphasized that the traditional culture of Arzamastsevo is a multi-component phenomenon, which is based on the original folklore of resettlers.